Nickel oxide nanoparticles exposure as a risk factor for male infertility: “In vitro” effects on porcine pre-pubertal Sertoli cells - Arato, Iva; Giovagnoli, Stefano; Di Michele, Alessandro; Bellucci, Catia; Lilli, Cinzia; Aglietti, Maria Chiara; Bartolini, Desirée; Gambelunghe, Angela; Muzi, Giacomo; Calvitti, Mario; Eugeni, Elena; Gaggia, Francesco; et al. (Frontiers in Endocrinology, 2023)
Lately, nickel oxide nanoparticles (NiO NPs) have been employed in many industrial and biomedical fields. Several studies have reported that NiO NPs may impair the development of reproductive organs inducing oxidative stress, which may result in male infertility. We investigated the in vitro effects of NiO NPs on porcine pre-pubertal Sertoli cells (SCs) which undergone acute (24 h) and chronic (from 1 up to 3 weeks) exposure at two subtoxic doses of NiO NPs of 1 μg/ml and 5 μg/ml. After NiO NPs exposure we performed the following analysis: (a) SCs morphological analysis (Light Microscopy); (b) ROS production and oxidative DNA damage, gene expression of antioxidant enzymes (c) SCs functionality (AMH, inhibin B Real-time PCR analysis and ELISA test); (d) apoptosis (WB analysis); (e) pro-inflammatory cytokines (Real-time PCR analysis), and (f) MAPK kinase signaling pathway (WB analysis). We found that the SCs exposed to both subtoxic doses of NiO NPs didn’t sustain substantial morphological changes. NiO NPs exposure, at each concentration, induced a marked increase of intracellular ROS at the third week of treatment and DNA damage at all exposure times. At both concentrations, the increased gene expression of antioxidant enzymes such as SOD and HO-1 was observed. AMH and inhibin B both gene expression and secretion significantly decreased at the third week at both concentrations of nanoparticles. Only the 5 μg/ml dose induced the activation of caspase-3 at the third week. At the two subtoxic doses of NiO NPs a clear pro-inflammatory stress was evaluated along with the steady increase in the gene expression of TNF-α and IL-6. Finally, an increased phosphorylation ratio of p-ERK1/2, p-38 and p-AKT was observed up to the third week, at both concentrations. Our results show the negative impact of subtoxic doses NiO NPs chronic exposure on porcine SCs functionality and viability.